The impact of energy consumption based on fossil fuel and hydroelectricity generation towards pollution in Malaysia, Indonesia and Thailand - Abdul Rahim Ridzuan; Aliashim Albani; Abdul Rais Abdul Latiff; Mohamad Idham Md. Razak; Mohd Haziq Murshidi (EconJournals, 2020)
This study investigated the effects of energy consumption (ENY) based on fossil fuels and alternative energy with hydroelectricity as its proxy upon pollution, aside from ascertaining if the correlation between income and pollution determined the presence of Environmental Kuznets curve (EKC). In addition, the functions of foreign direct investment (FDI) inflows and trade openness (TO) were probed into so as to generate more precise outcomes of EKC hypothesis. Hence, in order to fulfil the objectives outlined in this study, the Bound estimation method was utilized to examine three developing nations of the Association of South East Asian Nation (ASEAN), which are Malaysia, Indonesia, and Thailand. The main finding of interest retrieved from this paper refers to the EKC hypothesis reflective of Malaysia and Thailand. It was discovered that hydroelectricity favourably lowered the release of carbon emissions in the case of Malaysia, while it insignificantly influenced environmental degradation for Indonesia and Thailand. On the other hand, as anticipated, per capita energy use displayed a significant long-run effect in raising the levels of carbon emission in Indonesia and Thailand. Meanwhile, the FDI inflows seemed to improve the environmental quality only in Malaysia, while deepening in TO among ASEAN-3 nations appeared to successfully minimize issues related to environmental degradation in these countries.